Notes on some alpheid shrimps (Decapoda: Caridea) of Thalassia testudinum meadows, from the Central-Southern Mexican Caribbean - Román-Contreras, Ramiro; Martínez-Mayén, Mario (HIDROBIOLÓGICA, 2017)
This study provides an account of some shrimps of the family Alpheidae collected on Thalassia testudinum meadows in Bahía de la Ascensión, Bahía del Espíritu Santo and Mahahual reef lagoon, Quintana Roo, on the Caribbean coast of Mexico. A total of 657 specimens of alpheid shrimps were collected; they represent two genera and seven species. Alpheus was the most diverse genus with five species. An updated geographic distribution is provided for all the seven species recorded; four of them represent new records for Bahía del Espíritu Santo and two for the Mahahual reef lagoon.